2005
DOI: 10.1103/physrevlett.94.127003
|View full text |Cite
|
Sign up to set email alerts
|

Pairing and Superconductivity Driven by Strong Quasiparticle Renormalization in Two-Dimensional Organic Charge Transfer Salts

Abstract: We introduce and analyze a variational wave function for quasi two-dimensional κ-(ET)2 organic salts containing strong local and nonlocal correlation effects. We find an unconventional superconducting ground state for intermediate charge carrier interaction, sandwiched between a conventional metal at weak coupling and a spin liquid at larger coupling. Most remarkably, the excitation spectrum is dramatically renormalized and is found to be the driving force for the formation of the unusual superconducting state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
96
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 40 publications
(66 reference statements)
12
96
3
Order By: Relevance
“…The resulting Luttinger surface renormalizes to perfect nesting. A similar behavior has been observed in recent variational studies of organic charge transfer-salt superconductors (24). At half-filling the Hubbard model reduces to a spin model with NN J ϭ 4t 2 ͞U and a frustrating next NN JЈ ϭ 4(tЈ) 2 ͞U.…”
Section: Fs Renormalizationsupporting
confidence: 51%
“…The resulting Luttinger surface renormalizes to perfect nesting. A similar behavior has been observed in recent variational studies of organic charge transfer-salt superconductors (24). At half-filling the Hubbard model reduces to a spin model with NN J ϭ 4t 2 ͞U and a frustrating next NN JЈ ϭ 4(tЈ) 2 ͞U.…”
Section: Fs Renormalizationsupporting
confidence: 51%
“…It is well known that the perfect nesting of the square lattice means that is insulating for arbitrarily small U/t. For t = t, it is found, numerically, that the Mott transition occurs at around U/t = 10-15, depending on the method used [3,[15][16][17][18][19][20][21]79]. The metal-insulator transition line in Fig.…”
Section: Comparison With Organicsmentioning
confidence: 99%
“…This model contains three parameters: U the effective on-site Coulomb repulsion, t the nearest-neighbor hopping integral, and t the next-nearest-neighbor hopping integral along one diagonal only. The Hubbard model on the anisotropic triangular lattice has been studied via a number of approaches [15][16][17][18][19][20][21]. Some methods have suggested that a spin liquid is realized in the insulating phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantum Monte Carlo calculations [8] find enhanced dSC correlations. Ground state wave-functions obtained from variational methods [9] predict a transition between a dSC and a spin liquid phase, akin to a Mott transition, in the highly frustrated case. The spin liquid phase was also predicted by variational methods, and through a gauge theory of the Hubbard model [10].…”
mentioning
confidence: 99%